What Was Love? On the Dialectic of Mediation - Anders Johansson ([sic], 2017)
Love has traditionally been understood either as an objective, transcendentforce, or a subjective ability. Through a number of steps,the article argues that both these options have lost their credibility due to changes in the media through which love is performed. First, the article demonstrates how the attempts,in the life sciences, to explain love biologically or physically reproduce a traditional romantic ideology. Then, the implications of the inflation of explicit love declarations, and the consequences of internet dating, are discussed. What these examples amount to is the fact that the medium is brought to the fore. A consequence of this is that the romantic ideology is strengthened, while the premises of romantic love – the autonomous subject and the transcendent objectivity – are weakened or even dissolved.Keywords:idealism, materialism, narcissism, subjectivity, reification,internet dating, controlJennifer Lopez, Haddaway, Howard Jones – yes, virtually every singer, author,or philosopher since Sappho and Platohave raised the same question: What is love? This endless recurrence may be taken as a sign both of the aptness and inaptness of the question. The huge amount of answers makes it impossible to say anything that hasn’t already been said. Every love song is a cliché from the outset. On the other hand, the fact that the question keeps coming up over and over again, points to the endurance of the experience of or longing for love, and hence to the inevitability of the issue.